2014
DOI: 10.3346/jkms.2014.29.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy Case in a Newborn with Congenital Pulmonary Lymphangiectasia

Abstract: Congenital pulmonary lymphangiectasia (CPL) is a rare lymphatic pulmonary abnormality. CPL with respiratory distress has a poor prognosis, and is frequently fatal in neonates. We report a case of pneumonectomy for CPL in a newborn. An infant girl, born at 39 weeks' after an uncomplicated pregnancy, exhibited respiratory distress 1 hr after birth, which necessitated intubation and aggressive ventilator care. Right pneumonectomy was performed after her symptoms worsened. Histologic examination indicated CPL. She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…In general, the same causes of spontaneous miscarriage or early pregnancy failure are represented by various factors such as the mother's age, Chromosoma abnormalities, endocrine disorders, and thrombophilia. In addition to environmental factors and bacterial infections (22 ) , viral infections during pregnancy are dangerous for the fetus, such as being infected with rubella virus, Cytomegalovirus, and herpes simplex virus, as they are among the known causes of congenital anomalies and morbidity, and a recent study conducted in Korea by researchers ( 23) Coxsackievirus B is an important cause of forgotten miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the same causes of spontaneous miscarriage or early pregnancy failure are represented by various factors such as the mother's age, Chromosoma abnormalities, endocrine disorders, and thrombophilia. In addition to environmental factors and bacterial infections (22 ) , viral infections during pregnancy are dangerous for the fetus, such as being infected with rubella virus, Cytomegalovirus, and herpes simplex virus, as they are among the known causes of congenital anomalies and morbidity, and a recent study conducted in Korea by researchers ( 23) Coxsackievirus B is an important cause of forgotten miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with pneumonectomy has only been described in a newborn of 39 weeks of gestation with rightsided pulmonary lymphangiectasia and refractory respiratory insufficiency to the conventional treatment. The authors concluded that pneumonectomy can be considered for cases with unilateral CPL, with respira-tory insufficiency that is difficult to control and with a high probability of survival 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in the CPL both lungs are affected and have a poor prognosis with a mortality rate of 50-98% 8,9 . Unilateral presentation is extremely rare, only few cases have been reported, it has a better prognosis and sometimes it has a spontaneous resolution [10][11][12] . In both presentations, newborns present severe respiratory failure in the first hours of life and require support with conventional mechanical ventilation and in some cases with highfrequency oscillatory ventilation (HFOV) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The autopsy of neonates dead soon after birth in the delivery room should be performed in time to avoid disputes. CPLis a rare condition but has specific treatments for which include corticosteroids for patients with primary inflammatory conditions, dietary modifications, pneumonectomy, 27 octreotide, antiplasmin therapy, and fibrin glue pleurodesis.…”
Section: Vascular Diseasesmentioning
confidence: 99%